(untitled) (Bangladesh Journal of Animal Science, 2012)
A study was undertaken for the nutritional evaluation of Jambo forage by using Near Infrared Reflectance Spectroscopy (NIRS) and compare with the values obtained from wet chemistry analysis. Near infra-red reflectance spectrum of ground forage samples were obtained in duplicate (scanning number 32, resolution 8) with an FT-NIRS (Bruker, MPA, Germany) systems monochromator (700-2400 nm) using a Qurtz cup sampling device. For the development of local calibration equations, multivariate analysis was performed by a commercial analysis program Optical User Software (OPUS) and OpusLab to relate the spectral data and corresponding concentration values for each nutrient component of forage. The108 Jambo forage samples were collected from 108 cultivated experimental plots and ground through 2.0 mm screen for analysis the proximate components (Moisture, CP, CF, NFE and ash). The value for each component was placed into calibration group for NIRS equation development. The root mean square error of estimation (RMSEE) for the determination of CP, CF, NFE and total ash of Jambo forage was 0.33, 0.51, 1.14 and 0.39% respectively with correlation coefficient (r2) of 79.18, 82.04, 87.92 and 84.37 respectively. After cross validation, the root mean square error cross validation (RMSECV) for the CP, CF, NFE and total ash of Jambo forage were 0.37, 0.58, 1.41 and 0.48% respectively with correlation coefficient (r2) of 72.42, 73.85, 78.87 and 73.78 respectively. The mean predicted values of CP, CF, NFE and total ash by NIRS are close to the mean laboratory values determined by wet chemistry analysis. It can be concluded that NIRS could potentially be used to predict the nutritional quality of Jambo forage. DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10790 Bang. J. Anim. Sci. 2011. 40 (1-2): 46-50